The Effect of Taxation Understanding and Taxpayer Attitudes on Taxpayer Compliance with Implementation of E-Filing System as Mediation Variable - N L M Sugiartini; N S Hardika; N N Aryaningsih (Journal of Applied Sciences in Accounting, Finance, and Tax, 2020)
The tax revenues have not reached the target because the level of taxpayer compliance is still low. One of the efforts done by Direktorat Jenderal Pajak to improve taxpayer compliance is by implementing the e-filing system in tax reporting. The purpose of this study is to determine the effect of taxation understanding, and taxpayer attitudes on taxpayer compliance with implementation of e-filing system as mediation variable. The type of data used in this study are primary data obtained through questionnaires by respondents. The sample in the study was based on purposive sampling method with total sample of 100 individual taxpayers registered at the KPP Pratama Badung Selatan. Statistical testing used to test hypotheses was Partial Least Square (PLS) with SmartPLS 3.0. The results of this study showed that taxation understanding and the implementation of e-filing system have a positive and significant effect on taxpayer compliance. Taxpayer attitude has a negative and not significant effect on taxpayer compliance. Taxation understanding has a positive and significant effect on the implementation of e-filing system. Taxpayer attitude has a positive and not significant effect on the implementation of e-filing system. The implementation of e-filing system can mediate taxation understanding, and the implementation of e-filing systems cannot mediate taxpayer attitude on taxpayer compliance. The next research is expected to add other variables besides taxation understanding variable, taxpayer attitude, implementation of e-filing system, and taxpayer compliance.